Annual Plan 2005-06 Planning Commission Government of India, New Delhi - Planning Commission (Planning Commission, 2005)
The Tenth Five Year Plan (2002-07) has been formulated to carry on the consistent pursuit of the State to ensure employment generation, poverty reduction, improving the standard of living of its people and expanding and augmenting social and economic infrastructures. The Plan recognizes that its policies and programmes aimed at promoting faster economic growth must also foster the cause of distributive justice, rural development, regional balance and concern for the environment so that the benefits of growth are more evenly dispersed.
Planning Commission Government of India
Planning Commission Government of India